Rationale for Translational Research on Targeted Alpha Therapy in Japan —Renaissance of Radiopharmaceuticals Utilizing Astatine-211 and Actinium-225 - Yonekura, Yoshiharu; Fukase, Koichi; Hirabayashi, Yoko; Tatsumi, Mitsuaki; Hachisuka, Akiko; Yano, Tsuneo; Watabe, Tadashi; Fujii, Hirofumi; Kadonaga, Yuichiro; Sato, Tatsuhiko; Hasegawa, Koki; Kabayama, Kazuya (RADIOISOTOPES, 2020)
We wish to herewith report safety evaluations, microdosimetry, and clinical requirements for first-in-human (FIH) study for handling of targeted alpha therapy (TAT) drug products labelled by 211At and 225Ac. 1) The safety evaluation method is proposed including delayed toxicity using the histopathological examination. The biodistribution study using PET or SPECT corresponding to alpha nuclides is also proposed. 2) Two scales of microdosimetry are proposed for the TAT design; one is the organ-microstructure scales and the other is the cellular and subcellular scales. Recently, the stochastic microdosimetric kinetic model was developed by the cellular-scale particle transport simulation using PHITS. 3) The dose of TAT drug for FIH study can be considered in the amount of radioactivity and mass, and radioactivity would often be a more important determining factor than mass. 4) In Japan, Medical Device system for regulatory approval of the synthesizer itself has been adopted as well as Medical Drug system for delivery of radiopharmaceuticals. We propose to start an automatic synthesis device at an early stage and to establish manufacturing process, quality control and GMP evaluations. The need for radiation shielding based on the calculation by effective dose rate coefficients for alpha particles is also introduced. The argument is concluded that the operation in hot cell used at many PET centers is sufficient.